Christian Faith in Dialogue with Contemporary Culture in the Personalist Thought of John Paul II and Cardinal Stefan Wyszyński - Ficek, Ryszard (Verbum Vitae, 2021)
This article presents the intellectual legacy of both John Paul II and Cardinal Stefan Wyszyński as advocates of a personalist view of culture. Their teaching emphasizes the person and human dignity in striving for human self-fulfillment in a community seeking God’s transcendence. In this regard, their personalist vision of culture was defined in the context of the Second Vatican Council’s teaching. Therefore, the theological anthropology of both John Paul II and Cardinal Wyszyński is based on personalism, communion, dialogue, and freedom. Nevertheless, when God is marginalized by human activity, especially by the ideology of secularism and religious indifferentism, a severe cultural crisis arises. As a result, the dialogical character of the teaching of John Paul II and Cardinal Wyszyński in the dimension of Christian culture emphasizes inculturation and evangelization of human activity. On the other hand, the Christocentric and personalist context of their concepts reflects the theocentric and anthropocentric vision of culture, which, rooted in praxeological pastoral thought, displays their views on culture not only in the dimension of philosophical and theological doctrine but above all as a pastoral vision presenting Christian culture integrated with contemporary existential experience and focused on the perspective of “a new heaven and a new earth” (cf. 2 Cor 12:4; Rev 4:2–8; 21:2–10).